2016
DOI: 10.1016/j.ydbio.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

White paper on guidelines concerning enteric nervous system stem cell therapy for enteric neuropathies

Abstract: Over the last 20 years, there has been increasing focus on the development of novel stem cell based therapies for the treatment of disorders and diseases affecting the enteric nervous system (ENS) of the gastrointestinal tract (so-called enteric neuropathies). Here, the idea is that ENS progenitor/stem cells could be transplanted into the gut wall to replace the damaged or absent neurons and glia of the ENS. This White Paper sets out experts’ views on the commonly used methods and approaches to identify, isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 242 publications
3
131
1
Order By: Relevance
“…Our studies may explain why impaired motility (including constipation) is observed in HSCR patients after transitional zone pull-through (TZPT) (where part of the hypoganglionated gut remains after surgery) [43]. Additionally, our observations argue that the promise of successful treatment of long-segment HSCR by stem cell transplantation [4447], would require colonization of aganglionic gut segments along their full length. Further work using such zebrafish models has the potential to establish links between states of ganglionosis and their capacity to mediate peristalsis and other ENS regulated processes, and determine, for example, the minimal neurofunctional unit required to restore organized motility.…”
Section: Discussionmentioning
confidence: 93%
“…Our studies may explain why impaired motility (including constipation) is observed in HSCR patients after transitional zone pull-through (TZPT) (where part of the hypoganglionated gut remains after surgery) [43]. Additionally, our observations argue that the promise of successful treatment of long-segment HSCR by stem cell transplantation [4447], would require colonization of aganglionic gut segments along their full length. Further work using such zebrafish models has the potential to establish links between states of ganglionosis and their capacity to mediate peristalsis and other ENS regulated processes, and determine, for example, the minimal neurofunctional unit required to restore organized motility.…”
Section: Discussionmentioning
confidence: 93%
“…Given the missing heritability in Hirschprung disease, our results are also a suggestion to look for ErbB3 variants. Another possible clinical relevance is to neuropathic cases of chronic intestinal pseudoobstruction (43).…”
Section: Discussionmentioning
confidence: 99%
“…49 The existence of enteric neural stem cells in the postnatal or adult gut was once considered heretical but is now well documented, at least in animal models. 50 Most of the basic research has focused on myenteric ganglia and murine models. According to a recently published study, enteric neurons undergo postnatal homeostatic apoptosis and replacement by stem cells, 51 although this finding is controversial.…”
Section: Pathogenesis Of Ind Bmentioning
confidence: 99%